2018
DOI: 10.4314/ahs.v17i4.22
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic nephrotic syndrome in South African children.

Abstract: BackgroundDifferent histo-pathological types and treatment response patterns of Idiopathic nephrotic syndrome (INS) have been associated with differences in ethnicity and geographical location.ObjectiveTo provide an update on the steroid response and renal histo-pathological pattern in children treated for INS.MethodMedical records of children with INS treated at the Charlotte Maxeke Johannesburg Academic Hospital were reviewed.ResultsMean age was 5.3 years ± 2.8. The majority (68.1%) of the 163 children were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
(49 reference statements)
2
13
4
Order By: Relevance
“…B Prasun et al in their study on 88 children for 1 years found mean age on onset of NS to be 5.9±2.2 years while Bakhiet et al had 5.3±2.8 years as mean age of onset of NS in their study. 11,12 Our study male to female ratio was 2.23:1; El Bakkali et al13 study had male to female ratio of 2.9:1 while Other prospective study of 163 children done by Bakhiet et al 12 in Johannesburg, South Africa found out as 1.5:1, less compared to our study. This study was done in exclusive black race children and might have confounding effect.…”
Section: Discussioncontrasting
confidence: 60%
“…B Prasun et al in their study on 88 children for 1 years found mean age on onset of NS to be 5.9±2.2 years while Bakhiet et al had 5.3±2.8 years as mean age of onset of NS in their study. 11,12 Our study male to female ratio was 2.23:1; El Bakkali et al13 study had male to female ratio of 2.9:1 while Other prospective study of 163 children done by Bakhiet et al 12 in Johannesburg, South Africa found out as 1.5:1, less compared to our study. This study was done in exclusive black race children and might have confounding effect.…”
Section: Discussioncontrasting
confidence: 60%
“…approximately 70% of White children [9]. In New Orleans, USA, Kim showed that SRNS was four times more common in African Americans compared with children of European ancestry [12].…”
Section: Plos Onementioning
confidence: 99%
“…Studies in developed countries show good response to steroids in childhood nephrotic syndrome, with resistance seen more in Hispanics and Blacks (2,4,7). In Africa, nephrotic syndrome secondary to infections was previously considered predominant, with most reports favoring non-MCNS forms and lower steroid response rates (4,(8)(9)(10). However, studies in Southwest and Enugu state Nigeria reported a high steroid responsiveness of 82.5% and 85.7%, respectively (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertension, macroscopic hematuria, and decreased GFR, which are atypical features of nephrotic syndrome, occur more in secondary forms and are predictors of steroid resistance (2,9,14,16,17). Currently, an increasing trend of focal segmental glomerulosclerosis with concomitant increase in steroid resistance has been shown by studies in Caucasians, Asians, and as well as Africans (8,(18)(19)(20). Although studies exist in various regions elucidating the pattern of response to prednisolone in nephrotic syndrome patients, there are no studies in the Tigray region, Northern-Ethiopia.…”
Section: Introductionmentioning
confidence: 99%